2021
DOI: 10.1172/jci151697
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous bamlanivimab use associates with reduced hospitalization in high-risk patients with mild to moderate COVID-19

Abstract: Background: Clinical data to support the use of bamlanivimab for the treatment of outpatients with mild to moderate coronavirus disease-19 (COVID-19) is needed.Methods: 2,335 patients who received single-dose bamlanivimab infusion between November 12, 2020 to February 17, 2021 were compared with a propensity-matched control of 2,335 untreated patients with mild to moderate COVID-19 at Mayo Clinic facilities across 4 states.The primary outcome was the rate of hospitalization at days 14, 21 and 28. Results:The m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
53
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 21 publications
6
53
1
Order By: Relevance
“…Similar results were obtained by a large retrospective case‐control study noting all‐cause mortality reduction at day 21 among a group of high‐risk general patients who received bamlanivimab compared to a control group with mild to moderate COVID‐19 (0.05% vs. 0.4%; Risk Ratio‐RR, 0.13). 3 Furthermore, another real‐life clinical setting confirmed that NmAb (bamlanivimab or casirivimab/imdevimab) treatment significantly decreased hospital in‐patient status among a general population cohort with mild to moderate COVID‐19, especially when treatment was initiated ≤4 days after symptom onset. 4 …”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Similar results were obtained by a large retrospective case‐control study noting all‐cause mortality reduction at day 21 among a group of high‐risk general patients who received bamlanivimab compared to a control group with mild to moderate COVID‐19 (0.05% vs. 0.4%; Risk Ratio‐RR, 0.13). 3 Furthermore, another real‐life clinical setting confirmed that NmAb (bamlanivimab or casirivimab/imdevimab) treatment significantly decreased hospital in‐patient status among a general population cohort with mild to moderate COVID‐19, especially when treatment was initiated ≤4 days after symptom onset. 4 …”
Section: Discussionmentioning
confidence: 89%
“… 1 , 2 Similar results were obtained via retrospective case‐control studies regarding frequency reduction of hospitalizations. 3 , 4 …”
Section: Introductionmentioning
confidence: 99%
“… 11 , 12 Recently, several randomized controlled trials (RCTs) have been conducted to assess the clinical efficacy of neutralizing mABs for COVID‐19 patients, and they have shown promising results. 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 We conducted this systematic review and meta‐analysis of RCTs to provide robust and up‐to‐date evidence of the clinical efficacy and safety of neutralizing mABs for COVID‐19 outpatients.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 While these early studies did not initially evaluate transplant recipients, later observational studies found similar results in SOT recipients 11,12 and other high-risk populations. [13][14][15][16] In the setting of prior COVID-19 vaccination, however, it is less clear how effective these monoclonal antibody therapies may be.…”
Section: Introductionmentioning
confidence: 99%
“…Initial studies found this antibody therapy to reduce hospitalization and medically attended visits among patients with high‐risk comorbidities 9,10 . While these early studies did not initially evaluate transplant recipients, later observational studies found similar results in SOT recipients 11,12 and other high‐risk populations 13–16 . In the setting of prior COVID‐19 vaccination, however, it is less clear how effective these monoclonal antibody therapies may be.…”
Section: Introductionmentioning
confidence: 99%